Isopropanol Dehydration on Amorphous Silica–Alumina: Synergy of Brønsted and Lewis Acidities at Pseudo‐Bridging Silanols. Issue 1 (2nd December 2016) - Larmier, Kim; Chizallet, Céline; Maury, Sylvie; Cadran, Nicolas; Abboud, Johnny; Lamic‐Humblot, Anne‐Félicie; Marceau, Eric; Lauron‐Pernot, Hélène
Abstract: The mechanism of isopropanol dehydration on amorphous silica–alumina (ASA) was unraveled by a combination of experimental kinetic measurements and periodic density functional theory (DFT) calculations. We show that pseudo‐bridging silanols (PBS‐Al) are the most likely active sites owing to the synergy between the Brønsted and Lewis acidic properties of these sites, which facilitates the activation of alcohol hydroxy groups as leaving groups. Isopropanol dehydration was used to specifically investigate these PBS‐Al sites, whose density was estimated to be about 10 −1 site nm −2 on the silica‐doped alumina surface under investigation, by combining information from experiments and theoretical calculations. Abstract : Combining two types of acidity : Periodic ab initio calculations and kinetic measurements were combined to determine the catalytically active sites of isopropanol dehydration on amorphous silica–alumina. Pseudo‐bridging silanol sites, which are both Lewis and Brønsted acidic, were found to be of crucial importance in this process.